Patients with infusion-related reactions on fixed-dose rituximab treatment have higher body surface area than those without infusion-related reactions in adults with frequently relapsing minimal change nephrotic syndrome: a retrospective study - Hironobu Nishiura; Masaya Takahashi; Katsuhito Mori; Takashi Sugimoto; Masanori Emoto; Yasutaka Nakamura (BMC, 2024)
Abstract Background Infusion-related reactions (IRRs) are major side effects of rituximab administration. Male sex, high body weight, body surface area (BSA), and body mass index are predictive markers of rituximab-induced IRRs. However, as rituximab was not administered at a fixed dosage in a previous study, whether a higher dosage or factors associated with a larger physique are more strongly associated with rituximab-induced IRRs is unknown. Main body Thirteen adults with frequently relapsing minimal change nephrotic syndrome (MCNS) who received an initial rituximab dose of 500 mg between September 2015 and November 2022 were retrospectively evaluated. Data on IRRs were collected from medical records. The incidence of rituximab-induced IRRs was 38.5% (5/13). The IRR group had a significantly higher BSA than the non-IRR group (median, 1.86 vs. 1.48 m2; p = 0.045). Additionally, rituximab dosage normalized by BSA in the IRR group was significantly lower than that in the non-IRR group (median, 268.8 vs. 337.9 mg/m2; p = 0.045). Conclusions Our study revealed that adults with frequently relapsing MCNS who experienced IRRs tend to have a higher BSA, even with fixed-dose rituximab treatment. Therefore, when patients with higher BSA receive rituximab treatment, clinicians should be careful about monitoring patient condition whether the dosage is fixed or not.